The Synthesis of Unsymmetrical Arylated Tetrathiafulvalenes Extended with an Anthraquinoid Spacer via Pd-Catalyzed C–H Arylation - Yoshimura, Aya; Aso, Yuto; Utsumi, Ryosuke; Tosa, Fuma; Misaki, Yohji (Synlett, 2024)
We synthesized diarylated 10-(1,3-dithiol-2-ylidene)anthracene-9-(10H)-one derivatives, which serve as important precursors of unsymmetrical arylated TTFAQs, via the palladium-catalyzed direct C–H arylation. Unsymmetrical diarylated TTFAQs were synthesized by the Horner–Wadsworth–Emmons reaction using diarylated 10-(1,3-dithiol-2-ylidene)anthracene-9-(10H)-one as the starting materials. Additionally, we have successfully synthesized unsymmetrical tetraarylated TTFAQs by a second palladium-catalyzed C–H arylation of diarylated TTFAQs.
Keywords: tetrathiafulvalene; extended TTF; anthraquinoid spacer; unsymmetrical arylated compounds; palladium-catalyzed direct C–H arylation; X-ray structure analysis; redox behavior